ANALISIS KEMAMPUAN SISWA MENYELESAIKAN MASALAH MATEMATIKA NON-RUTIN PADA KONSEP PERBANDINGAN SENILAI - Arma Wangsa; Marniati Marniati; Sufri Mashuri; Nuralda Nuralda (Jurnal Riset Guru Indonesia, 2026)
This study was conducted to explain students' ability to solve non-routine mathematics problems using the concept of direct proportion. To achieve this objective, a descriptive qualitative paradigm was employed, with seventh-grade students of SMP Negeri 25 Poleang Barat as the research subjects. Data were collected by administering a test consisting of one non-routine mathematics problem and conducting diagnostic interviews. Based on the collected data, three students were purposively selected, each representing high, medium, and low ability levels, and were analyzed based on Polya’s problem-solving stages using the flow model technique. The results showed that students in the high and medium ability categories were able to solve the non-routine problem involving the concept of direct proportion and fulfilled all four indicators (understanding information, devising a plan, carrying out the plan, and evaluating the solution). Meanwhile, students in the low ability category demonstrated poor performance. Students in this category were only able to meet the indicator of understanding problem information but failed to meet the other three indicators (devising and carrying out a plan, and evaluating the solution). Furthermore, it was also found that students showed conceptual understanding (high-ability category) and semi-conceptual understanding (medium-ability category) in the process of problem solving.